Health service factors affecting the COVID-19 vaccination campaign in a Ghanaian metropolis: A qualitative exploratory study - Susanna Aba Aba Abraham; Gifty Osei Berchie; Dorcas Obiri-Yeboah; John Oti Amoah; Dorcas Frempomaa Agyare; Deogratias Kaheeru Sekimpi; Diana Bosomtwe-Duker; Andrews Adjei Druye (BMJ Open)
Objective The study sought to explore the perspectives of vaccinators on the health system factors that impacted the COVID-19 vaccination campaign.Design The study employed an exploratory-descriptive qualitative design. Key-informants’ interviews were conducted using semi-structured guide to gather the data. Thematic analysis following the steps of Braun and Clark was conducted using ATLAS.ti software.Setting The study setting was the Cape Coast Metropolis where the Central Regional Health Directorate is located. The Directorate initiates and implements policy decisions across the region. It is also the only metropolis in the region that recorded about 5970 of the total COVID-19 cases recorded in Ghana.Participants Eleven vaccinators who had been trained for the COVID-19 vaccination and had participated in the campaign for at least 6 months were purposively sampled through the Regional Public Health Unit.Results Four themes were derived from the data after analysis; ‘vaccine-related issues’; ‘staffing issues’; ‘organising and planning the campaign’ and ‘surveillance and response systems’. Subthemes were generated under each major theme. Our results revealed the health service promoted the COVID-19 vaccination campaign through public education and ensured access to COVID-19 vaccines through the use of community outreaches. Also, the health service ensured adequate logistics supply for carrying out the campaign as well as ensured vaccinators were adequately equipped for adverse incidence reporting and management. Dissatisfaction among COVID-19 vaccinators attributed to low remuneration and delays in receiving allowances as well as shortfalls in efforts at securing transportation and a conducive venue for the vaccination exercise also emerged. Other challenges in the vaccination campaign were attributed to poor data entry platforms and limited access to internet facilities.Conclusion This study highlights the health system’s strategies and challenges during the COVID-19 vaccination campaign, emphasising the need for critical interventions to prevent low vaccination rates.